Non-Invasive Respiratory Impedance Enhances Cerebral Perfusion in Healthy Adults - Favilla, Christopher G.; Parthasarathy, Ashwin B.; Detre, John A.; Yodh, Arjun G.; Mullen, Michael T.; Kasner, Scott E.; Gannon, Kimberly; Messé, Steven R. (Frontiers in Neurology, 2017)
Optimization of cerebral blood flow is the cornerstone of clinical management in a number of neurologic diseases, most notably ischemic stroke. Intra-thoracic pressure influences cardiac output and has the potential to impact cerebral blood flow. Here we aim to quantify cerebral hemodynamic changes in response to increased respiratory impedance using a non-invasive respiratory device. We measured cerebral perfusion under varying levels of respiratory impedance (6cm H20, 9cm H20, and 12 cm H20) in 20 healthy volunteers. Simultaneous measurements of microvascular cerebral blood flow and middle cerebral artery mean flow velocity, respectively, were performed with optical diffuse correlation spectroscopy and transcranial Doppler ultrasound. At a high level of respiratory impedance, mean flow velocity increased by 6.4% compared to baseline (p=0.004), but changes in cortical cerebral blood flow were non-significant. In a multivariable linear regression model accounting for end tidal CO2, respiratory impedance was associated with increases in both mean flow velocity (coefficient: 0.49, p<0.001) and cortical cerebral blood flow (coefficient: 0.13, p<0.001), although the magnitude of the effect was small. Manipulating intrathoracic pressure via non-invasive respiratory impedance was well tolerated and produced a small but measurable increase in cerebral perfusion in healthy individuals. Future studies in acute ischemic stroke patients with impaired cerebral autoregulation is warranted in order to assess whether respiratory impedance is feasible as a novel non-invasive therapy for stroke.